Spatial, Temporal, and Demographic Patterns in the Prevalence of Hemorrhagic Septicemia in 41 Countries in 2005–2019: A Systematic Analysis with Special Focus on the Potential Development of a New-Generation Vaccine - Reyad Almoheer; Mohd Effendy Abd Wahid; Hidayatul Aini Zakaria; Mohd Anuar Bin Jonet; Muhanna Mohammed Al-shaibani; Adel Al-Gheethi; Siti Nor Khadijah Addis (Vaccines, 2022)
Hemorrhagic septicemia (HS) caused by Pasteurella multocida B:2 and E:2 is among the fatal bacterial diseases in cattle and buffaloes that are economically valuable in Asian and African countries. The current work aims to study the prevalence of HS among buffaloes, cattle, sheep, and goats in 41 countries in 2005–2019. The data analysis revealed that 74.4% of the total infection rate in the world was distributed among cattle, followed by buffaloes (13.1%). The mortality of HS among cattle and buffaloes increased in 2017–2019 compared to the period between 2014 and 2016. The best measure to control the disease is through vaccination programs. Current commercial vaccines, including live-attenuated vaccines and inactivated vaccines, have some shortcomings and undesirable effects. Virus-like particles (VLPs) have more potential as a vaccine platform due to their unique properties to enhance immune response and the ability to use them as a platform for foreign antigens against infectious diseases. VLPs-based vaccines are among the new-generation subunit vaccine approaches that have been licensed for the human and veterinary fields. However, most studies are still in the late stages of vaccine evaluation.